Zasoby martwego drewna w lasach miejskich Warszawy - Skwarek, Konrad; Skwarek, Konrad; Bijak, Szymon; Bijak, Szymon (Leśne Prace Badawcze, 2015)
Dead wood plays an important role for the biodiversity of forest ecosystems and influences their proper development. This study assessed the amount of coarse woody debris in municipal forests in Warsaw (central Poland). Based on the forest site type, dominant tree species and age class, we stratified all complexes of the Warsaw urban forests in order to allocate 55 sample plots. For these plots, we determined the volume of dead wood including standing dead trees, coarse woody debris and broken branches as well as uprooted trees. We calculated the amount of dead wood in the distinguished site-species-age layers and for individual complexes. The volume of dead matter in municipal forests in Warsaw amounted to 38 761 m 3 , i.e. 13.7 m 3 /ha. The obtained results correspond to the current regulations concerning the amount of dead organic matter to be left in forests. Only in the Las Bielański complex (northern Warsaw) volume of dead wood is comparable to the level observed in Polish national parks or nature reserves, which is still far lower than the values found for natural forests. In general, municipal forests in Warsaw stand out positively in terms of dead wood quantity and a high degree of variation in the forms and dimensions of dead wood.